Spatial Adaptability Pattern of Riverside Kampong Communities in Gang Nibung Samarinda - Rizky Nur Rahman; Ima Defiana; Sri Nastiti Nugrahani Ekasiwi (Center for Scientific Publication, 2022)
Each settlement has specific characteristics and characteristics based on their respective backgrounds. Gang Nibung Samarinda is an urban kampong settlement on the banks of the Karang Mumus River of Samarinda City. Characteristics of riverside settlements are different from settlements that do not have rivers, these characteristics can be reviewed from how the community adapts to be able to use space on housing and environment in riverside city villages. The community adapts to be able to meet its needs causing changes in residential space and environmental space. Characteristics of the condition of the Gang nibung settlement site, which is mainly surrounded by rivers, make the orientation of occupancy facing towards the river makes the space on the riverbank becomes used space for its people. This study uses field study methods in reviewing space adaptation activities in riverside villages. This research uses field study methods in reviewing space adaptation activities in the riverside village environment. The results showed that the adaptability pattern of space is influenced by the pattern of the type of clarity of the activity that is accommodated, the pattern of openness of the design of a space, and the pattern of the relationship of space with the surrounding environment.